Bed Particle Displacements and Morphological Development in a Wandering Gravel‐Bed River. Issue 2 (12th February 2021) - McQueen, R.; Ashmore, P.; Millard, T.; Goeller, N.
Abstract: Bed particles were tracked using passive integrated transponder tags in a wandering reach of the San Juan River, British Columbia, Canada, to assess particle movement around three major bars in the river. In‐channel topographic changes were monitored through repeat LiDAR surveys during this period and used in concert with the tracer data set to assess the relationship between particle displacements and changes in channel morphology, specifically, the development and re‐working of bars. This has direct implications for virtual velocity and morphologic based estimates of bedload flux, which rely on accurate estimates of the variability and magnitude of particle path lengths over time. Tracers were deployed in the river at three separate locations in the Fall of 2015, 2016, 2017, and 2018, with recovery surveys conducted during the summer low‐flow season the year after tracer deployment and multiple mobilizing events. Tracers exhibited path length distributions reflective of both morphologic controls and year to year differences related to the annual flow regime. Annual tracer transport was restricted primarily to less than one riffle‐pool‐bar unit, even during years with a greater number of peak floods and duration of competent flow. Tracer deposition and burial was focused along bar margins, particularly at or downstream of the bar apex, reflecting the downstream migration and lateral bar accretion observed on Digital Elevation Models of difference. This highlights the fundamental importance of bar development and re‐working underpinning bedload transport processes in bar‐dominated channels. Key Points: Annual bed particle displacements reflect morphologic controls and differences in the annual flow regime Bed particle transport and burial is directly tied to patterns of bar‐scale erosion and deposition Tracer deposition focused along bar margins, primarily at or downstream of the first downstream bar apex